Evolution, characterization and phylogenetic utility of ITS2 gene in Orthoptera and some Polyneoptera: Highly variable at the order level and highly conserved at the species level - Uluar, Onur; Çiplak, Battal (Zootaxa, 2020)
ITS2 is often suggested as a potential marker for evolutionary studies and species barcoding. However, there are many lineages have not been studied. This study focuses on ITS2 in Polyneoptera at the order and species levels. ITS2 sequences representing six polyneopteran orders and 15 species in the genus Anterastes are studied. We arrived at the following conclusions: (i) ITS2 is highly variable and contains little phylogenetic information in Polyneoptera, (ii) the shortest length and the highest GC content of ITS2 is found in Orthoptera among insects, (iii) the secondary structure exhibits general characteristics of eukaryotes especially in helices II and III, and with no order-specific architecture, (iv) ITS2 is highly conserved at the species level, both in linear sequences and secondary structures, (v) helices I, IA, II, IIA and III almost invariable in nucleotide sequence shared by all species in the genus. At the generic level, the most conspicuous result is the variable pattern in ITS2. It is highly conserved in helical sequences, but highly variable in non/peri-helical regions which we considered to be mutation islands. These frequently mutated regions contain a significant amount of molecular homoplasy, thus, the utility of ITS2 in phylogenetic analyses and species barcoding is low, at least in Polyneoptera.